Trainer styles: a situational approach - Bharath, G. (2002)
The manner in which a trainer handles the participants' queries and interactions during the training session has an immense effect on the whole training. Trainers need to adapt their approaches or styles depending on the situation or the entry behaviour of learners. Though this entry behaviour may vary widely with a heterogeneous grop of learners, a trainer is nevertheless expected to adapt the training style to suit all the participants. Hence, it is imperative for the trainer to develop some understanding about the `Readiness level' of every learner so that s/he is able adapt the training style to effectively handle the interactions and meet the learner's requirements as well. To effectively adapt one's training style, the trainer should (1) know what factors determine the readiness level of learners (2) be able to judge the level of learners' readiness (3) be aware of the response styles that are at one's disposal and (4) be able to choose the appropriate style depending on the situation. The readiness level of the learner will basically depend on two factors: (1) the learner-trainer knowledge gap and (2) the learner willingess. What are termed as sam, dhan, bhed and dand in ancient Sanskrit Literature can be used as power bases for the trainer. Sam, dhan, bhed and dand are Sanskrit words meaning treating as equal, reward, discrimination and punishment respectively. They are said to have been recommended as stra tegies by our ancient epic Mahabharat and Kautilya's Artha Shastra (the Science of Polity) for dealing with the opponents. The author has been applying the concept of sam, dhan, bhed and dand in training situations, as imbued from his early school teacher. The author has built a model, which, he believes, will be of practical help to training practitioners. The article attempts to give some suggestions for evaluating the readiness state of the learners in a classroom and recommends training styles/approaches that would be appropriate for different readiness states of learners. The author draws the inspiration for building this model Situational Leadership Model of Paul Hersey and Kenneth Blanchard and he owes his gratitude to them for their book "Management of Organizational Behaviour." - Reproduced.
Keywords: Training